Emerging Role of Ferroptosis in the Pathogenesis of Ischemic Stroke: A New Therapeutic Target?. (August 2021) - Bu, Zhong-Qi; Yu, Hai-Yang; Wang, Jue; He, Xin; Cui, Yue-Ran; Feng, Jia-Chun; Feng, Juan
Ischemic stroke is one of the main causes of high morbidity, mortality, and disability worldwide; however, the treatment methods are limited and do not always achieve satisfactory results. The pathogenesis of ischemic stroke is complex, defined by multiple mechanisms; among them, programmed death of neuronal cells plays a significant role. Ferroptosis is a novel type of regulated cell death characterized by iron redistribution or accumulation and increased lipid peroxidation in the membrane. Ferroptosis is implicated in many pathological conditions, such as cancer, neurodegenerative diseases, and ischemia-reperfusion injury. In this review, we summarize current research findings on ferroptosis, including possible molecular mechanisms and therapeutic applications of ferroptosis regulators, with a focus on the involvement of ferroptosis in the pathogenesis and treatment of ischemic stroke. Understanding the role of ferroptosis in ischemic stroke will throw some light on the development of methods for diagnosis, treatment, and prevention of this devastating disease.